PSYCHOLOGICAL AND PEDAGOGICAL FEATURES OF TEACHING ENGLISH IN PRIMARY SCHOOLS - Әкімханқызы, Назерке (Вестник ЗКУ, 2022)
The aim of the modernization process in contemporary Kazakhstan education is to shape the personality from the socialization of an individual, who is a bearer of culture of his time and nation. According to the updated educational standard, the English language should be considered not only as a medium of instruction. Especially when learning English in the primary schools, new psychological and pedagogical approaches and methods should be widely used. In the article the competence of the subject of English studied in the primary grades was considered. Also, today was analyzed the relationship of psychological and pedagogical features in the process of teaching English to elementary schoolchildren with different approaches of the subject methodology. Emphasis was placed on the fact that the purpose of teaching English in the primary school is not only to transfer knowledge and skills in a foreign language to students, but also to form certain qualities of personality.